Red and Black Flat Mite, A False Spider Mite, Brevipalpus phoenics (Geijskes) (Arachnida: Acari: Tenuipalpidae) - Harold A. Denmark; Thomas R. Fasulo (EDIS)
EENY-381, a 5-page illustrated fact sheet by H. A. Denmark and Thomas R. Fasulo, is included in the Featured Creatures series. It describes this mite with extensive host range and potential for economic damage, its synonymy, distribution, description, hosts, economic importance, management, and selected references. Published by the UF Department of Entomology and Nematology, July 2006.